Acute effects of mindful interval exercise on cognitive performance in a higher education setting. (January 2023) - Kao, Shih-Chun; Baumgartner, Nicholas W.; Pritt, Tyler; Wu, Sabrina; Schmitt, Sara; Ullrich-French, Sarah; Wang, Chun-Hao
Abstract: Interval exercise (IE) has been shown to have acute facilitating effects on cognition; however, the existing literature has been limited to laboratory settings and has focused on manipulating the parameters of exercise bouts during IE. This study included two classroom-based experiments to (1) investigate the effect of an acute bout of IE delivering mindfulness activity during its recovery intervals (mindful IE) on cognitive performance, and (2) compare cognitive performance following acute bouts of mindful IE with non-mindful IE. Experiment 1 : Using a class-based within-subject crossover design, 59 participants completed the Stroop, d2, and trail-making tests to measure inhibitory control, attention, and cognitive flexibility, after a 30-min non-exercise or mindful IE session on separate counterbalanced days. Experiment 2 : Using a similar design, 70 participants were assigned to two groups to receive a non-exercise and an IE session with (mindful) or without (non-mindful) mindfulness-based recovery intervals on separate counterbalanced days. Results from Experiment 1 showed superior d2 performance following the mindful IE than the non-exercise session. Although Experiment 2 found exercise-related decreases in commission error rate during the d2 test in both groups, the non-mindful group showed additional decreases in omission and total error rates. Further, higher scores on the nonreactivity facet of dispositional mindfulness were correlated with larger decreases in omission and total error rates during the d2 test for the mindful IE group. No exercise-related effect was found for outcomes of the Stroop and trail-making tests in both experiments. These findings in the selective improvements in d2 test performance are the first to suggest the feasibility of integrating mindfulness activity into the recovery intervals of IE for enhanced cognitive performance that may depend on individual differences in dispositional mindfulness. Highlights: Classroom-based intense interval exercise (IE) has acute benefits to attention. Delivering mindful recovery during IE leads to less comprehensive attentional gains. Attentional gains from mindful IE depends on trait mindfulness.